(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La vicenda - 2. Gli argomenti pro e contro l’elezione di un sacerdote a Rettore di una università pubblica - 3. Le incompatibilità dei ministri di culto - 4. La possibile incidenza dei principi riguardanti la c.d. “laïcité d’apparence” - 5. L’intervento dei giudici amministrativi - 6. Conclusioni: l’irrilevanza dell’ordinazione non accompagnata dall’esercizio di funzioni ministeriali. The election of a Catholic priest as Rector of the University of Strasbourg: “Much ado about nothing”? ABSTRACT: This study examines the question of compatibility between the principle of neutrality of public services in force in French law and the election of a minister of the Catholic religion as Rector of a public university. The Author rules out the existence of any form of incapacity. However, since the duty of discretion of the public official (“devoir de réserve”) operates even outside the exercise of his functions, it may limit the freedom to exercise pastoral ministry in specific cases, as well as the performance of the most typical tasks that are inherent in the status of minister of worship, due to the inevitable repercussions on the image of the university.